Menstrual migraine - pathophysiology, clinical features and treatment options - Szczotka, Dominika; Opala, Dominika; Osuch, Dobromiła; Staszczyk, Izabela; Drabik, Aleksandra; Szemplińska, Antonina; Błachnio, Klaudia; Anderska, Agnieszka (Quality in Sport, 2024)
Introduction and purpose: Migraine is a prevalent neurological disorder, affecting significantly more women, especially during their childbearing years, due to its unique link to the menstrual cycle. Over 50% of women with migraines report a connection between their attacks and menstruation. This review aims to highlight the latest data on the pathophysiology, epidemiology, and treatment of menstrual migraines, emphasizing the need for increased attention to this condition. Materials and Methods: A literature review was conducted using PubMed and Google Scholar, with search phrases including menstrual migraine, migraine, menstruation, migraine diagnosis, migraine treatment, and non-pharmacological migraine treatments. Current Knowledge: Misinterpretation of diagnostic criteria results in conflicting information about the incidence, clinical characteristics, and treatment response of menstrual migraines. Furthermore, clinical studies often do not differentiate perimenstrual attacks. The role of ovarian hormones, particularly estrogen, in the pathogenesis of menstrual migraines complicates treatment efforts. Summary: Due to the common and debilitating nature of the menstrual migraine, more detailed research is essential to expand our understanding of its pathophysiology and to develop more effective treatments. Understanding the mechanisms behind menstrual migraines may lead to new treatment options targeting this specific condition.